The Influence of Short Video Content on Brand Awareness and Customer Loyalty with Customer Engagement as a Moderating Variable (A Study on Ocha in Banyuwangi) - Nilawati, wardha (GREENOMIKA, 2025)
This research aims to analyze the influence of short-form video content on brand awareness and customer loyalty with customer engagement as a moderating variable in the Ocha beverage business in Banyuwangi. The advancement of digital technology and the proliferation of social media platforms such as TikTok and Instagram have transformed the way brands interact with consumers. Short-form video content is considered effective in building brand awareness through visual appeal and emotional messages that are brief yet powerful. However, the success of this strategy is significantly influenced by the level of customer engagement, which serves as a reinforcement of the relationship between brand awareness and customer loyalty. This research is expected to provide theoretical contributions to the development of digital marketing literature as well as practical contributions for MSMEs (Micro, Small, and Medium Enterprises) in designing communication strategies based on short-form videos.